Isolasi, Identifikasi, Karakterisasi Dan Uji Toksisitas Senyawa Metabolit Sekunder Fraksi Nonpolar Akar Babandotan (Ageratum conyzoides L) - Irmawan, Muhammad; Mandey, Frederyk; Dali, Seniwati (Indonesian Journal of Chemical Research, 2018)
Ageratum Conyzoides L. has a toxic and bioactive component as anti-cancer and especially for the root, it has anti-tumor. In order to figure out the active component, it is necessary to do four steps; isolation, identification, characterization, and toxicity essay Brine Shrimp Lethality Test (BSLT) of non-polar fraction Ageratum conyzoides L plant. Isolation method consist of four parts; extraction, partitioning of Kupchan method, fractionation, and purification. Fractionation method uses press column chromatography (KTT). Furthermore, purification process uses thin layer chromatography (TLC) and characterization with spectroscopy FTIR, 1H-NMR and 13C-NMR. Then characterization utilizes spectroscopy FTIR, 1H-NMR and 13C-NMR. The toxicity essay toward Artemia Salina Leach n-hexane fraction and dichloromethane fraction showed that the fraction had toxic properties with number of LC50 are 0,0237 and 4,642 µg/mL respectively. Moreover, n-hexane fraction has succeed in isolating Stigmasterol compound shaped white crystalline needles with 19.6 mg weight, 143-144 °C melting point and and had toxic properties with number of LC50 are 30,33 µg/mL.